ID-Map (Interactive Digital Map) - Yakup, Mohd Rafee; Awangko Hamdan, Awang Arshad; Sylvester Wielding, Jussem; Hishamuddin, Siri; Poline, Bala; Mohamad Zamhari Hassan, Abol; Doris, Maying.; Sarah Naemah, Aman Leong; Siti Zulaiha, Md Yusof; Anyshya, Jusam; Yu, Wei Chow (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
The invention of Interactive Digital Map (iD-MAP) is to establish, display and relay information of rural village and its dwellers to the visitors; serving as a one-stop center that delivers all the information related to the uniqueness and tourism products of the village. The establishment of a digital tourism system based on digital and interactive multimedia technology will develop and enhance the competitiveness and rapid development of rural and cultural tourism industry. At the same time, the system also is an artistic approach created for a more reliable storage, accessible record and to ease the retrieval of information for future development. Additionally, iD-MAP is a response to the unorganized and unpresentable condition of the existing visitor information board located at the entrance of Pa’ Lungan in Bario. This invention is an interactive and informative digital mapping using a technology that superimposes a digitally-generated image on the user’s view with the intention to provide and share required visuals and hence, providing a composite view of the displayed materials. This highly informative digital map using digital mapping and Augmented Reality (AR) to illustrate the location of local tourist attraction, available public facilities, prominent landmarks as well as the mean in locating the locality of each house in the village. The retrieval of the desired information is made possible with the usage of the smart phone equipped with the selected AR Apps. The establishment of iD-MAP based on digital and interactive multimedia technology will develop and enhance the competitiveness and rapid development of rural tourism industry. This acts also as a response towards supporting the key economic sectors within the Digital Economy initiatives by the Government of Sarawak.